Effectiveness Of Criminal Sanctions Against Perpetrators Of Narcotics Crime - Siregar, Fernandus; Hasibuan, Syaiful Asmi (International Publisher, 2023)
Increased supervision and control as an effort to prevent and eradicate drug abuse and illicit trafficking is very necessary, because crime in this field is growing both in terms of quality and quantity. Drugs have troubled our society in Indonesia because the effects of this object if consumed incorrectly and excessively by its users will be fatal, it can also result in death for its users. The research objectives are 1) Knowing the effectiveness of criminal sanctions against perpetrators of narcotics crimes. 2) Knowing the obstacles faced in increasing the effectiveness of enforcement of criminal law sanctions against perpetrators of narcotics crimes.3) Knowing the efforts made to increase the effectiveness of enforcement of criminal law sanctions against perpetrators of narcotics crimes. The approach used in this research is empirical juridical approach. This research is descriptive research. The types of data used are primary data and secondary data using primary, secondary and tertiary legal materials. This library research is conducted by searching, collecting, and studying laws and regulations and other legal materials related to the object of research. From the results of the study, namely that the increase in the number is not too large, it may be said that the punishment process has been effective. The factors inhibiting law enforcement of narcotics crimes committed by the police: Facility factors related to the problem of inadequate facilities and infrastructure and limited budget support. The community factor and the lack of public concern to report to the authorities make it difficult for law enforcers to eradicate narcotics crime The most effective and basic methods of preventing and eradicating drug abuse are promotive and preventive methods. The most practical and real efforts are repressive and humane efforts are curative and rehabilitative.